Editorial: chronic DILI and HILI – corticosteroid plus glycyrrhizin as standard therapy?. Issue 1 (10th June 2022) - Teschke, Rolf; Eickhoff, Axel
LINKED CONTENT: This article is linked to Wang et al papers. To view this article, visit https://doi.org/10.1111/apt.16902 and https://doi.org/10.1111/apt.16983